An aesthetics of law and culture : text, images, screens - Kenyon, Andrew T.; Rush, Peter, 1959- (Studies in law, politics, and society, 2004)
This special volume of "Studies in Law, Politics, and Society - The Aesthetics of Law and Culture: Texts, Images, Screens"--Examines practices of representation and their relation to juridical and cultural formations. The chapters range across the media of speech and writing, word and image, legislation and judgment, literature, cinema and photography. The contributions draw on disciplines including jurisprudence, literary criticism, philosophy, cinema studies, art and visual studies, cartography, historiography and medicine. They are ordered according to four prominent themes in contemporary, theoretically informed critical scholarship: Crime Scenes: Sexuality and Representation; Sites Unsaid: Testimony, Image, Genre; (Post) Colonial Appropriations; and Screen Culture: Sovereignty, Cinema and Law.